(3)x*x+11x+6=0

Simple and best practice solution for (3)x*x+11x+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3)x*x+11x+6=0 equation:


Simplifying
(3) * x * x + 11x + 6 = 0

Multiply x * x
3x2 + 11x + 6 = 0

Reorder the terms:
6 + 11x + 3x2 = 0

Solving
6 + 11x + 3x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(3 + x)(2 + 3x) = 0

Subproblem 1

Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(2 + 3x)' equal to zero and attempt to solve: Simplifying 2 + 3x = 0 Solving 2 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 0 + -2 3x = 0 + -2 Combine like terms: 0 + -2 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667

Solution

x = {-3, -0.6666666667}

See similar equations:

| 2-3(x-5)=-7(x+1) | | 100-2m= | | 5x-10-4x+15=45 | | 3x*3x+11x+6=o | | 2[5-(x-12)]=x-14 | | 3y-7=-5y-39 | | x-.85x=84 | | 2(x-5)-5(7-x)=9 | | 6(2x+1)=3x-7x | | (3z+7)(3-z)=0 | | 3y-9=24+3y | | 10-2x=7x+37 | | -2=6a+3-5 | | 2z^2-4z=0 | | 3x-4(x+11)=-2(x+8)-43 | | +3--4= | | 6-7x-3(x+3)=1-8x | | 7+3x=2x-2 | | 5x-2x=3x | | 4x+8-3=2x-6 | | 3x-(x+31)+(1-x)=-63 | | 7(2x+6)-4(2x-3)=13x+9 | | -1-6v=2+7(7+v) | | (x-3)(x+4)=(x+1)(x+6) | | 6y-12=10+-5y | | -2(3x+5)=4(x-6) | | 6-4(3+x)+2(x-3)=-16 | | 18v^3+51v-42v= | | z^2-16z+39=0 | | -(n-5)=25 | | -14+32x+128x^2=0 | | 2x+5=7x-55 |

Equations solver categories